Diplomasi RI di Mesir dan Negara-Negara Arab pada Tahun 1947 - Rahman, Suranta Abd. (UI Scholars Hub, 2007)
In 1947, the Republic of Indonesia (RI) sent a diplomatic mission to seek the international community's acknowledgement for the nation's independence. The mission in the Arab nations, particularly in Egypt, was severely challenged by the Netherlands. However, with a spirit of solidarity, the people and government of Egypt supported the struggle and acknowledged RI's independence, de facto and de jure. Diplomacy was implemented in maintaining RI's sovereignty which was threatened to be retaken by the Netherlands. Meanwhile, the struggles in military area were maintained to dissipate the Netherlands from Indonesia.